RANCANG BANGUN SISTEM INFORMASI GEOGRAFIS DENGAN FUZZY MULTIPLE CRITERIA DECISION MAKING UNTUK PEMILIHAN LOKASI PRIORITAS UNTUK PENGEMBANGAN PERUMAHAN DAN PERMUKIMAN DI KAWASAN BLORA - Joko Handoyo; Agus Darwanto; Suprawikno Suprawikno (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2014)
Housing and Settlement is one of the basic human needs in order to improve people's welfare and equity . No real problems facing aspects develops regardless of the dynamics of public life and government policy in managing existing problems . In addressing the issue of housing and settlements , each process is implemented gradually through the stages of the preparation , planning , implementation , management , maintenance , and development . The software has been created it can be used to solve decision-making to some alternative decisions to be taken with some of the criteria that will be taken into consideration by using Fuzzy Multiple Criteria Decision Making to get a decision alternative with the highest priority as an optimal alternative . The software has been created it can be used to solve the decision to seek the determination of the optimal location for residential development based on criteria SNI 03-1733-2004 . From the test results it can be concluded that by using Fuzzy Multiple Criteria Decision Making can be set on locating residential development consisting of three integral alternative location . Integral is the location of diagnosis results obtained optimal location , with a degree of optimism either 0 , 0.5 and 1